The modification of T description according to visceral pleural invasion and tumor size from 3.1 cm to 4.0 cm in non-small cell lung cancer: A retrospective analysis based on the SEER database. (August 2021) - Qi, Mengfan; Bian, Dongliang; Zhang, Jing; Zhu, Xinsheng; Zhou, Caicun; Zhang, Lei
Highlights: Visceral pleural invasion (VPI) proved to be an independent prognostic factor of NSCLC patients. NSCLC patients with stage pT2aN0M0 and VPI positive have no significant difference of OS compared with those stage pT2bN0M0. VPI was significantly related with age, gender, differentiation grade and tumor size. Abstract: Objectives: As a poor prognostic factor, visceral pleural invasion (VPI) was incorporated into non-small cell lung cancer (NSCLC) staging system. For modifying the T description of NSCLC, the prognostic value of VPI was assessed. Materials and Methods: From 2010–2015, data on stage pT2N0M0 NSCLC patients with tumor size (TS) from 3.1 cm to 5.0 cm who received surgery from the Surveillance, Epidemiology, and End Results (SEER) database were enrolled retrospectively. Propensity score matching was utilized to balance the baseline factors according to different TS intervals. Overall survival (OS) was assessed by the Kaplan-Meier method and log-rank test. Univariate and multivariate analysis were applied to identify the prognostic factors. The risk factors of VPI were calculated by logistic regression model. Result: The sum of 4005 resected stage pT2N0M0 NSCLC patients with TS from 3.1 cm to 5.0 cm were recruited, which had 1084 patients with VPI and 2921 patients without VPI respectively. As TS interval of 3.1−4.0 cm, the 5-year OS of patients without VPI was significantly better than those with VPI (62.6 % vs 58.7 %, P = 0.015), while the 5-year OS of patients with VPI and TS interval of 3.1−4.0 cm had no significant difference compared with patients whose TS interval of 4.1−5.0 cm (58.7 % vs 58.8 %, P = 0.918). Logistic regressive analysis manifested that older age, female, worse differentiation grade and larger TS had higher incidence of VPI (OR = 1.01, 1.25, 1.25, 1.16, respectively; P < 0.05 for all). Conclusion: This study underlined the prognostic effect of VPI and suggested that early-stage NSCLC with VPI and TS interval of 3.1–4.0 cm could be appropriately upstaged from pT2a (stage pIB) to pT2b (modified stage pIIA).